Suppression of NOD-like receptor protein 3 inflammasome activation and macrophage M1 polarization by hederagenin contributes to attenuation of sepsis-induced acute lung injury in rats. Issue 3 (1st March 2022) - Wang, Lin; Zhao, Min
ABSTRACT: Acute lung injury (ALI) is a major leading cause of death in sepsis patients. Hederagenin (HG), derived from Hedera helix Linné, has anti-inflammatory effects, while its role in sepsis-induced ALI has not been elucidated. In vivo, rats were subjected to cecal ligation and puncture to induce ALI and then treated with HG (12.5, 25, or 50 mg/kg) by gavage. Administration of HG raised survival rate, ameliorated lung injury, and decreased lung wet/dry ratio and inflammatory cell accumulation in bronchoalveloar lavage fluid (BALF) of ALI rats. HG inhibited macrophage polarization toward the M1 phenotype as evidenced by decreased CD86 expression in rat lung tissues. Moreover, HG decreased the secretion of TNF-α, IL-6 and monocyte chemoattractant protein-1 (MCP-1) in BALF and the levels of inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) in lung tissues. In vitro, phorbol-12-myristate-13-acetate (PMA)-differentiated THP-1 macrophages were stimulated with 100 ng/mL lipopolysaccharide. HG treatment inhibited M1 macrophage polarization and the production of M1-related pro-inflammatory mediators (IL-6, MCP-1, iNOS, and COX-2). Mechanistically, HG inhibited NLRP3 inflammasome activation and subsequent release of IL-18 and IL-1β, and suppressed NF-κB signaling pathway both in vivo and in vitro . Notably, HG treatment further emphasized the inhibitory effect of NF-κB inhibitor BAY11-7082 on NLRP3 inflammasome activation and macrophage M1 polarization. Taken together, HG exerts a protective effect against sepsis-induced ALI by reducing the inflammatory response and macrophage M1 polarization, which may involve NF-κB pathway-modulated NLRP3 inflammasome activation. Graphical abstract: uf0001